Limits of Detection of Topically Applied Products in the Skin Using In Vivo Raman Spectroscopy - Cláudio Nico; Tom C. Bakker Schut; Peter J. Caspers; Gerwin J. Puppels (MDPI AG, 2024)
We have developed a method to determine the limit of detection (LoD) for quantitative measurement of exogenous analytes in the outer layer of the human skin by in vivo confocal Raman spectroscopy. The method is in accordance with the guidelines of the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use that have been adopted by regulatory authorities such as the American Food and Drug Administration and the European Medicines Agency. The method can be applied in silico so that the limit of detection can be assessed before starting a skin penetration study, for example, in areas of pharmaceutical formulation, pharmacokinetics, or toxicokinetics. This can significantly reduce the need for expensive and time-consuming feasibility studies. This paper describes the method to calculate this LoD as well as the experimental and methodological factors that can influence the calculation of the LoD.